Distinctive Urbanization in The Peri-Urban Regions of East and Southeast Asia: Renewing the Debate - McGee, Terry (Journal of Regional and City Planning, 2005)
This paper re-opens the discussion on the issue on urbanization of peri-urban region in east and south Asia. Its distinctive features as compared to those in western countries brought criticism mainly on the concept of extended urbanization that characterized the urbanization in developing Asian countries. There are some critical reflections that will be considered to answer that criticism mainly the very basic arguments of the extended metropolis, among others the regional diversity in the urbanization trajectories and internal differentiation that is emerging in the contemporary extended metropolitan in the region.  After looking back at the definition of the peri-urban region and their importance in the countries, and a case study of Guangdong in China, a policy challenges are raised.Keywords: urbanization, peri-urban, extended metropolitan, East and Southeast Asia